COMMUNITY BASED DOMESTIC WASTE PRODUCT MANAGEMENT IN SORAGAN NGESTIHARJO KASIHAN BANTUL YOGYAKARTA - Benny Hartanto (Sekolah Tinggi Maritim Yogyakarta, 2018)
The problem of domestic waste in Soragan has not completely been solved by Bantul municipal government. The government has realized this problem, however, it has not found an appropriate long term solution. The objectives of the research on community-based waste management are (1) to describe a community-based domestic waste management in Soragan Bantul municipality, (2) to identify the problems in the community-based domestic waste management, and (3) to recommend the solutions for improving the community-based domestic waste management. The research was conducted in Soragan in which a pilot project of the community-based domestic waste management has been initiated. The descriptive qualitative research was employed in this research. Data were collected with interview, questionnaire, observation, and documentation. The collected data were validated and analyzed qualitatively. The findings of the research are as follows :. Firstly, the pilot project of the community-based domestic waste management in Soragan, Bantul municipality has successfully been carried out by using 3R (reduce, reuse, recycle) principle and has reduced the amount of waste in Temporary Waste Dumping (TPS) up to 73%. Secondly, the community-based domestic waste management using 3R principle is a paradigmatic solution. Thirdly, the main problem of carrying out the community-based domestic waste management is how to change old paradigm of “throwing out the waste” to “managing the waste”. The other identified problems are : (1) the municipal government has not appreciated the people who have been sorting domestic waste; (2) there is no mechanism and person to supervises and evaluates the management; (3) the management has not been provided with supporting facilities and infrastructures; (4) sorting domestic waste has not really been completed; (5) people do not form new cadres who have capability and integrity to manage waste. There are six recommendations to manage domestic waste. Firstly, the government, RT boards, and managers plan to facilitate people measurably how to sort domestic waste properly. Secondly, the government organizes and gives incentive and disincentive to encourage people. Thirdly, the government, RT boards, and managers make a mechanism and appoint persons to supervise and evaluate the management. Fourthly, the government provides facilities and infrastructures to support the management. Fifthly, managers and RT boards find strategies to form new cadres who have capability and integrity to manage waste. Sixthly, the community-based domestic waste management is a suitable model developed in urban areas.